Guest water hinders sodium-ion diffusion in low-defect Berlin green cathode material. Issue 38 (14th September 2022) - Ojwang, Dickson O.; Häggström, Lennart; Ericsson, Tore; Mogensen, Ronnie; Brant, William R.
Abstract : Removal of H2 O from BG significantly improves the cycling stability. The least hydrated electrode has the fastest D Na + of 7.30 × 10 −12 cm 2 s −1 and capacity of ∼60 mA h g −1, compared to 2.92 × 10 −12 cm 2 s −1 and ∼40 mA h g −1 for the more hydrated one. Abstract : Among Prussian blue analogues (PBAs), Na x Fe[Fe(CN)6 ]1− y · n H2 O is a highly attractive cathode material for sodium-ion batteries due to its high theoretical capacity of ∼170 mA h g −1 and inexpensive raw materials. However, concerns remain over its long-term electrochemical performance and structural factors which impact sources of resistance in the material and subsequently rate performance. Refined control of the [Fe(CN)6 ] vacancies and water content could help in realizing its market potential. In this context, we have studied a low-defect Berlin green (BG) Na0.30(5) Fe[Fe(CN)6 ]0.94(2) · n H2 O with varied water content corresponding to 10, 8, 6, and 2 wt%. The impact of water on the electrochemical properties of BG was systematically investigated. The electrodes were cycled within a narrow voltage window of 3.15–3.8 V vs. Na/Na + to avoid undesired phase transitions and side reactions while preserving the cubic structure. We demonstrate that thermal dehydration leads to a significantly improved cycling stability of over 300 cycles at 15 mA g −1 with coulombic efficiency of >99.9%. In particular, the electrode with the lowest water content exhibited the fastest Na + -ion insertion/extraction as evidenced by the larger CV peak currents during successive scans compared to hydrated samples. The results provide fundamental insight for designing PBAs as electrode materials with enhanced electrochemical performance in energy storage applications.